Laclau and Mouffe's Discourse Theory: Professionalism as an Empty Signifier for Nursing - Ramsey, Sarah M. (Nursing philosophy, 2025)
Chantal Mouffe and Ernesto Laclau made significant developments in discourse theory, based on the premise that all practices and objects are discursive, deriving meaning through existence in a wider context. This paper introduces the work of Laclau and Mouffe, explicating the main tenets of discourse theory through an example chosen from the nursing discourse, "professionalism", and exploring how this serves as an empty signifier. The construction of a discourse is explored, from the building blocks of individual signs and moments to the totality established when each sign is fixed in relation to other signs and all other possible meanings excluded. The empty signifier represents a lack or absence, stabilising the discourse in a move towards hegemony. The question is posed as to whether, as an empty signifier, professionalism has resulted in a successful hegemonic formulation. Nursing has always struggled to be "fully constituted" with an antagonistic frontier delineating "women's work" of caring and nurturance from the cost-effectiveness of evidence-based practice. However, the lack of a coherent identity for nursing is highlighted as the empty signifier defines us merely as "not unprofessional". Identification of the empty signifier "professionalism" and exploration of the ensuing hegemonic formation of "professional" nursing identity demonstrates that the work of Laclau and Mouffe has significant relevance to nursing. Exploration of further areas of the nursing discourse through the lens of discourse theory is encouraged.